UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH OPINI AUDITOR, PROFITABILITAS, DAN DEBT TO EQUITY RATIO TERHADAP AUDIT DELAY - Subawa Putra, Putu Gede Ovan; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2016)
This study aims to determine the influence of the auditor's opinion, profitability, and debt to equity ratio to audit delay, and to determine whether the size of the company's moderate the relationship between the auditor's opinion on the audit delay, the profitability of the audit delay, as well as the debt to equity ratio to audit delay. This study uses data analysis techniques Moderated Regression Analysis with a total sample of 36 companies manufacturing various industry sectors listed on the Indonesia Stock Exchange with the observation period 2012 to 2014, bringing the total to 108 sample observations. The results showed that the auditor's opinion, profitability, and debt to equity ratio effect on audit delay. Moderate size company (strengthen) the impact of the auditor's opinion on the audit delay. However, the size of the company is not able to moderate the effect of profitability on audit delay, as well as the debt to equity ratio to audit delay.
Keywords: The Size Of The Company, Auditor' s Opinion, Profitability, Debt To Equity Ratio, Audit Delay